2019
DOI: 10.1093/mnras/stz2086
|View full text |Cite
|
Sign up to set email alerts
|

Elemental and molecular abundances in comet 67P/Churyumov-Gerasimenko

Abstract: Comets are considered to be some of the most pristine and unprocessed solar system objects accessible to in-situ exploration. Investigating their molecular and elemental composition takes us on a journey back to the early period of our solar system and possibly even further. In this work, we deduce the bulk abundances of the major volatile species in comet 67P/Churyumov-Gerasimenko, the target of the European Space Agency's Rosetta mission. The basis are measurements obtained with the ROSINA instrument suite o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
189
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(218 citation statements)
references
References 98 publications
15
189
2
2
Order By: Relevance
“…A detailed comparison with thermochemical disk models is necessary to distinguish between the two competing scenarios. Finally, the [CH 3 OH]/[H 2 CO] abundance ratio in all disks except HD 163296 is comparable with the wide range found for comets 67P/C-G, Hale-Bopp, and Lovejoy (∼0.65−8, Biver et al 2015;Rubin et al 2019), even though IRAS 04302 sits at the lower limit of that range. The comparison in Fig.…”
Section: Discussionsupporting
confidence: 77%
“…A detailed comparison with thermochemical disk models is necessary to distinguish between the two competing scenarios. Finally, the [CH 3 OH]/[H 2 CO] abundance ratio in all disks except HD 163296 is comparable with the wide range found for comets 67P/C-G, Hale-Bopp, and Lovejoy (∼0.65−8, Biver et al 2015;Rubin et al 2019), even though IRAS 04302 sits at the lower limit of that range. The comparison in Fig.…”
Section: Discussionsupporting
confidence: 77%
“…For this period, the comet was at heliocentric distances smaller than 2 AU, the Sun in the southern hemisphere and before the close perihelion period with a lot of short lived outbursts. Measurements during this period yielded relative abundances of NH3/H2O = (0.66 ±0.20) % and HCN/H2O = (0.14 ± 0.04) %, respectively (18), in line with the average comet (1). From figure 1a it is evident that during perihelion the NH3/H2O ratio is higher than further from the Sun and that there is quite some scattering in the ratio, reaching values of almost 3 %, uncorrelated with latitude/season ( fig.…”
supporting
confidence: 53%
“…We consider them "uncorrelated" to ammonium salt. (b) elemental abundances in comets Halley (red) and 67P (purple) for a refractory to ice ratio of 1:1, compared to the Sun, meteorites (C1, C2, and C3, refer to type 1, type 2, and type 3 carbonaceous chondrites) and the Earth (after Rubin et al (18)). N* denotes the nitrogen abundance if we assume that most of the nitrogen is in ammonium salt and the dust/ice ratio is 1:1 (see text for an explanation).…”
Section: Fig 4: Abundance Ratios Normalized To Watermentioning
confidence: 99%
“…Separately listed are relative abundances of 67P/C-G from Table 2 measured by VIRTIS (range given by green boxes; Bockelée-Morvan et al 2016), MIRO (black;, and ROSINA (red, different isomers may be present, e.g. HCN cannot be distinguished from HNC with ROSINA; Rubin et al 2019a) Figure 1 shows in blue boxes the abundance range of commonly observed volatile species with respect to water in comets. Shown is a selected set of species detected in at least 3 comets aside from 67P/C-G.…”
Section: Abundances Of Volatile Species In Comets and Classificationmentioning
confidence: 99%
“…This period, when Rosetta was passing rather closely over the then-active southern summer hemisphere and outbursts were still limited (Vincent et al 2016), was identified by Calmonte et al (2016) to be suitable to estimate bulk abundances. This approach assumes that the high erosion rate of the comet leads to relative abundances of the gases in Table 2 Measured coma abundances or abundance ranges by number (in % normalized to water) for a suite of volatile molecules from in situ ROSINA observations in May/June 2015 before perihelion (Rubin et al (2019a) and references therein) and via remote sensing by MIRO, integrated over the 2 years Rosetta followed the comet , VIRTIS-H at perihelion (Bockelée-Morvan et al 2016), and Alice from ∼2 au inbound to 2.5 au outbound (Keeney et al 2017). Species observed by mass spectrometry may (also) be present in the form of different isomers (cf.…”
Section: P/c-g Abundances Of Volatiles and Refractoriesmentioning
confidence: 99%